Identifying the Nutritional Properties of Australian Kabuli Chickpeas to Inform Future Novel Food Product Development - Chatur, Prakhar (Curtin University, 2021)
Australia is a major global chickpea producer, however there is a lack of information on physical, nutritional and antioxidant properties of Australian Kabuli chickpeas. These seed properties are also affected by the growing environment and processing method used to make chickpeas more palatable for human consumption. Thus, seed properties of Australian Kabuli chickpeas and the effects of growing environment and innovative high pressure processing on these properties were explored.